High prevalence of methicillin resistance and PVL genes among Staphylococcus aureus isolates from the nares and skin lesions of pediatric patients with atopic dermatitis - Cavalcante,F.S. (2015)
Staphylococcus aureus is highly prevalent among patients with atopic dermatitis (AD), and this pathogen may trigger and aggravate AD lesions. The aim of this study was to determine the prevalence of S. aureus in the nares of pediatric subjects and verify the phenotypic and molecular characteristics of the isolates in pediatric patients with AD. Isolates were tested for antimicrobial susceptibility, SCCmec typing, and Panton-Valentine Leukocidin (PVL) genes. Lineages were determined by pulsed-field gel electrophoresis and multilocus sequence typing (MLST). AD severity was assessed with the Scoring Atopic Dermatitis (SCORAD) index. Among 106 patients, 90 (85%) presented S. aureus isolates in their nares, and 8 also presented the pathogen in their skin infections. Two patients had two positive lesions, making a total of 10 S. aureus isolates from skin infections. Methicillin-resistant S. aureus (MRSA) was detected in 24 (26.6%) patients, and PVL genes were identified in 21 (23.3%), including 6 (75%) of the 8 patients with skin lesions but mainly in patients with severe and moderate SCORAD values (P=0.0095). All 24 MRSA isolates were susceptible to trimethoprim/sulfamethoxazole, while 8 isolates had a minimum inhibitory concentration (MIC) to mupirocin >1024 μg/mL. High lineage diversity was found among the isolates including USA1100/ST30, USA400/ST1, USA800/ST5, ST83, ST188, ST718, ST1635, and ST2791. There was a high prevalence of MRSA and PVL genes among the isolates recovered in this study. PVL genes were found mostly among patients with severe and moderate SCORAD values. These findings can help clinicians improve the therapies and strategies for the management of pediatric patients with AD.